LINGUISTIC ASPECTS OF CYBER COMMUNICATION IN ENGLISH AND UZBEK LANGUAGES - Vokhidova Tamanno Saidjonovna (University Research Base, 2024)
This article is devoted to the study of linguistic aspects of cybercommunication in English and Uzbek, as well as Internet terms and their comparison. This study is carried out through a continuous selection of Internet terms from scientific articles, online dictionaries, and online communications between computer users. The author gives a classification of terms according to various parameters and conducts an in-depth analysis of borrowing, tracing and word formation of Internet terms.